2023
DOI: 10.1007/s11104-023-05986-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of climate change on pasture quality in Mediterranean dehesas subjected to different grazing histories

Abstract: Background and aims Forecasted climate change and overgrazing are threatening the sustainability of dehesas, human-managed ecosystems where pastures, livestock and scattered trees coexist. Pasture quality is particularly sensitive to these global-change drivers, but there are still many gaps to broaden knowledge about the interactive effects of both factors on it. In addition, scattered trees might play a relevant role in maintaining high levels of pasture quality under future scenarios of higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 100 publications
0
2
0
Order By: Relevance
“…A simulation of the effects of climate change on farms in New Zealand showed that, in the absence of adaptation strategies, the effects of climate change would negatively impact pasture growth, which would then have an effect on farm profits overall (Kalaugher et al, 2017). Furthermore, changes in temperature and rainfall patterns will impact pasture quality by altering the concentration of P and Ca2+ (Hidalgo et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…A simulation of the effects of climate change on farms in New Zealand showed that, in the absence of adaptation strategies, the effects of climate change would negatively impact pasture growth, which would then have an effect on farm profits overall (Kalaugher et al, 2017). Furthermore, changes in temperature and rainfall patterns will impact pasture quality by altering the concentration of P and Ca2+ (Hidalgo et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…Beyond their economic contributions, these pastures also serve as habitat and food sources for a wide range of faunal species, including storks, vultures, lynx, eagles, lizards, and cranes, among others, contributing to the rich biodiversity of the region [4]. Agroforestry systems, including dehesas, are vital for carbon sequestration and biodiversity preservation [5][6][7][8][9]. Appropriate agroforestry management practices, including sustainable grassland-livestock systems and legume incorporation, are essential for increasing productivity and diversity, especially under increased climate variability [10].…”
Section: Introductionmentioning
confidence: 99%